Comparison and Analysis of MPEG-DASH and HLS Adaptive Streaming Delivery Tecbnology - Guqiao Zhu; Hao Song (Dianxin kexue)
The principle of HTTP adaptive streaming delivery technology with the representative of MPEG-DASH and HLS solution was researched.It focuses on technical characteristics comparison by the viewpoint of user experience and system efficiency.By analyzing industrial chain development and system evolution,the feasibility and prospect of MPEG-DASH deployment were further discussed.